Maxillary Hollow Denture: A Case Series - Kaira, Laxman Singh (Journal of Orofacial Research, 2012)
Retention, stability and support are the basic principles on which the success of a complete denture relies on. The skill lies in applying these principles efficiently in critical situations. Residual ridge resorption occurs at a three times faster rate in mandibular arch than in the maxillary arch. The severely resorbed maxillary and mandibular edentulous arches that are narrow and constricted with increased interarch space provide decreased support, retention and stability. The consequent weight of the processed complete denture only compromises them further. The severely resorbed jaw can have various treatment option. This clinical report describes three case reports of an edentulous patients with resorbed ridges where a simplified technique of fabricating a light weight hollow maxillary complete denture was used for the preservation of denture bearing areas.